EFEKTIFITAS TUGAS TIM PENGAMAT PEMASYARAKATAN DALAM MENCAPAI TUJUAN SISTEM PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN KLAS II A PEKANBARU BERDASARKAN UNDANG - UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - ROBERTO SIANTURI; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Society system that is founded by Saharjo said that purposes of prision criminal is in additional to losing freedom move, to educate prisioner to be repent, to educaye being good member of society. To achieve the goal of this society system is formed by society observer team who has the duty as to give suggestion about shape and coaching and guidance programme in doing society system, to make assesment on implementation of coachong and guidance programme and receive complaint and denunciation from citizens coaching people. In fact, in society organization class II A, Pekanbaru, the duty can not be yet served well and it can be known the benefit by citizens coaching people. The purposes of process of writing thesis is to know. First, how effectiveness the duty of society observer team in achieving purpose of society. Second, what are obstacles that is faced by society observer team in achieving the purpose of society system. Third, the effort that is done to overcome the obstacles that are faced by society observer tean in achieving the purpose of society systemThis research used kind of research Yuridis sosiologis that is seen by correlation between law and society. This research is done in society organization class II A pekanbaru, meanwhile population and sample is all of sides that relate with the problem that is researched. In this research, the source of data is used primer data, sekundar data and tertier data, technique for collecting the data in this research are interview, literature, and questionerBased on the result, there are three main things that can be concludedFirst, the implementation of duty of society observer team do not already work effectively. It is because the existence of society observer team that is less known by not only citizens coaching people but also wide society. So, in operating the duty, society observer team do not yet work maximal in achieving the purpose of society system. Second, the obstacles in implementing the duty of society observer team are qualitu and quantity of member of society observer team who is not enough, tool and infrastructure, and awareness of that prisioner.Third, the effort in overcoming the obstacles of implementation the duty of society system team is to carry on so that quality and quantity of member of society observer team in order to be able to answer defiances and problems that is appear, to being maximal using of routine calculation Lapas/ Rutan/ Cabrutan in m.a 250 to help the prisoner has low economy with coaching and guidance of citizens coaching people to follow rules and order of society system.Keywords: Effectiveness - Correctional - Society System